Contrasting Regional Carbon Cycle Responses to Seasonal Climate Anomalies Across the East‐West Divide of Temperate North America. Issue 11 (13th November 2020) - Byrne, B.; Liu, J.; Bloom, A. A.; Bowman, K. W.; Butterfield, Z.; Joiner, J.; Keenan, T. F.; Keppel‐Aleks, G.; Parazoo, N. C.; Yin, Y.
Abstract : Across temperate North America, interannual variability (IAV) in gross primary production (GPP) and net ecosystem exchange (NEE) and their relationship with environmental drivers are poorly understood. Here, we examine IAV in GPP and NEE and their relationship to environmental drivers using two state‐of‐the‐science flux products: NEE constrained by surface and space‐based atmospheric CO2 measurements over 2010–2015 and satellite up‐scaled GPP from FluxSat over 2001–2017. We show that the arid western half of temperate North America provides a larger contribution to IAV in GPP (104% of east) and NEE (127% of east) than the eastern half, in spite of smaller magnitude of annual mean GPP and NEE. This occurs because anomalies in western ecosystems are temporally coherent across the growing season leading to an amplification of GPP and NEE. In contrast, IAV in GPP and NEE in eastern ecosystems is dominated by seasonal compensation effects, associated with opposite responses to temperature anomalies in spring and summer. Terrestrial biosphere models in the MsTMIP ensemble generally capture these differences between eastern and western temperate North America, although there is considerable spread between models. Key Points: GPP and NEE IAV in western temperate North America is characterized by amplification, with enhance uptake in cooler‐wetter conditions GPP and NEE IAV in eastern temperate North America is characterized by compensating anomalies between spring and summer The MsTMIP models generally capture these east‐west differences in NEE and GPP IAV